Study of Ballistic Graphene Nanoribbon FET and Carbon Nanotube FET for device applications - Pavel, Md. Reaz Haider (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.